Risk Factors for Problematic Behaviors among Forensic Outpatients under the Medical Treatment and Supervision Act in Japan - Ando, Kumiko; Soshi, Takahiro; Nakazawa, Kanako; Noda, Takamasa; Okada, Takayuki (Frontiers in Psychiatry, 2016)
The Medical Treatment and Supervision Act (MTSA) was enacted in 2005 in Japan to promote the reintegration of clinical offenders with mental disorders into society. Under the MTSA, individuals who committed serious crimes in a state of insanity or diminished responsibility are diverted from the criminal justice system to the mental health system. Based on court decisions about MTSA-based treatment, clinical offenders have an obligation to engage in rehabilitation within their local community under the guidance of mental health professionals. However, patients under MTSA-based clinical treatments have faced various problems in the course of treatment, because of psychiatric as well as other static or dynamic factors, and sometimes have committed problematic behaviors, such as violence and medical non-compliance. Hence, this study aimed to clarify factors related to patients' inclusion in MTSA-based outpatient treatment and additionally, their commitment of problematic behaviors, based on confidential data acquired during a four-year government survey period (National Center of Neurology and Psychiatry) from MTSA enactment (July 15, 2005) to December 31, 2009. In total, we recruited 441 clinical offenders receiving MTSA-based outpatient treatment from 158 nationwide facilities. To evaluate related factors, we collected demographic, psychiatric, forensic, clinical treatment, and social service information. Statistical analyses demonstrated that predominant profiles of patients included male gender, younger age, low school history, psychiatric diagnoses (F1, F2, and F3), and no correctional or outpatient history before MTSA-based treatment. F1 or substance use diagnosis, in particular, was increasingly correlated with other factors, such as male gender, older age, and correctional history before MTSA treatment. Among the 441 patients, 189 (43%) committed problematic behaviors in the course of the MTSA-based outpatient treatment. Risk factors for patients' commitment of problematic behaviors comprised F1 diagnosis and inpatient history before MTSA-based treatment inclusion. In summary, reduction of overall problematic behaviors under the MTSA outpatient likely makes progress by focal attention to patients with psychiatric disorders caused by substance use and/or a past inpatient history for more severe psychiatric symptoms. This work is of ongoing and future importance in the domain of forensic community treatment, to connect risk-enhancing factors with risk management.